THE USE OF THE CAPABILITIES OF MODERN DIGITAL TECHNOLOGIES IN ACADEMIC LYCEUMS (ON THE EXAMPLE OF THE SCIENCE” INFORMATICS AND INFORMATION TECHNOLOGY") - Kulidjanova Yulduzxon Inomjon qizi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
Today, in the educational process, the emphasis is on using the capabilities of Web technologies to improve the quality of classes. Thus, students need to create elecrton educational resources so that they can independently master classes using Web technologies to further their interest in subjects. This article covers the effective use of web technologies in the lessons.